Mer-Hagography: The Erasure, Return and Resonance of Splash’s Older Mermaid - Hayward, Philip (Text Matters: A Journal of Literature, Theory and Culture, 2021)
The 1984 feature film Splash initially included a scene featuring an embittered, older mermaid (referred to as the “Merhag” or “Sea-Hag” by the production team) that was deleted before the final version premiered. Since that excision, the older mermaid and the scene she appeared in have been recreated by fans and the mer/sea-hag has come to comprise a minor element in contemporary online culture. The term “Merhag,” in particular, has also spread beyond the film, being taken up in fantasy fiction and being used—allusively and often pejoratively—to describe notional and actual female characters. Drawing on Mary Daly’s 1978 exploration of supressed female experiences and perspectives, this essay first examines Splash and associated texts with regard to the general figure of the hag in western culture (and with regard to negative, ageist perceptions of the ageing female), before discussing the use of “Merhag” and “Sea-Hag” as allusive pejoratives and the manner in which their negative connotations have been countered.